Numerical Simulation of Micro Gravitational Hydro-turbine for Alternative Renewable Energy Resources in Rural Area - Muhammad Fikri, Musthapa; Azfarizal, Mukhtar; Mohamad Fariz, Mohamed Nasir*; Ahmad Faiz, Tharima (INTI International University, 2020)
Hydropower is one of the most reliable and efficient sources for the clean generation of renewable energy. The increase of energy demand in developing countries has caused the extensive grow of hydropower development. In this light, the usage of low head hydro vortex turbine has been considered as a solution for the shortage of energy supply in rural areas. To alleviate the shortage of energy supply, it is essential to fabricate a Micro Gravitational Hydro-turbine which allows the conversion of energy in a moving fluid to rotational energy through the use of low head and low flow rate with a relatively simple structure. Thus, we attempt to analyse the maximum output power of the suggested model. The model was numerically simulated using commercial CFD software. Different geometrical basin designs are being developed as well as the simulations are varied with different flow rate parameter. The findings indicated that the maximum output generated via the conical basin is 630.01 W while the cylindrical basin is 27.47 W. It is shown that the conical basin design could increase power production and able to operate efficiently at a different flow rate. In general, the current work could be used as a replacement for the traditional small water turbine design in Malaysia.